2020
DOI: 10.1007/s11065-020-09449-1
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Learning in Individuals with Amnestic Mild Cognitive Impairment and Alzheimer’s Dementia: a Systematic Review and Meta-analysis

Abstract: The notion that procedural learning and memory is spared in Alzheimer’s disease (AD) has important implications for interventions aiming to build on intact cognitive functions. However, despite these clinical implications, there are mixed findings in the literature about whether or not procedural learning remains intact. This meta-analysis examines the standard mean difference of all published studies regarding procedural learning in AD dementia or amnestic Mild Cognitive Impairment (aMCI) compared to cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…In AD, episodic memory, which is retrieved in consciousness, mediated by words, is impaired from the early stage, but procedural memory, which does not use conceptual representation, is spared, even in severe AD patients who have lost their language skills, as shown by the present results. Recent systematic reviews and meta-analyses have suggested that procedural memory, which is the memory of perceptual-motor skills that can be evaluated based on rotary pursuit tasks and other methods, can be acquired even in patients with Alzheimer’s disease ( De Wit et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In AD, episodic memory, which is retrieved in consciousness, mediated by words, is impaired from the early stage, but procedural memory, which does not use conceptual representation, is spared, even in severe AD patients who have lost their language skills, as shown by the present results. Recent systematic reviews and meta-analyses have suggested that procedural memory, which is the memory of perceptual-motor skills that can be evaluated based on rotary pursuit tasks and other methods, can be acquired even in patients with Alzheimer’s disease ( De Wit et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not appear to be the case. While declarative memory is impaired early on in AD (Libon et al, 1998), procedural memory remains more or less intact until the later stages of the disease (De Wit et al, 2021). When we consider that participants do not actually perform any actions and see the events from a third‐person point of view, combined with the fact that impairment can be observed in the very early stages of the disease, it is likely that this paradigm taps largely into declarative memory rather than procedural.…”
Section: Discussionmentioning
confidence: 99%
“…In AD, episodic memory, which involves conscious recollection using words, is impaired from an early stage. However, a recent systematic meta-analysis has suggested that procedural memory, which does not involve the use of language representation skills, is maintained even in AD patients 18) .…”
Section: Table 2 Situations In Which Ms X Was Distracted and Not Distracted From Eatingmentioning
confidence: 99%